Selecting and weighting dynamical models using data-driven approaches - Le Bras, Pierre (2024)
In geosciences, multi-model ensembles are helpful to explore the robustness of a range of results. Toobtain a synthetic and improved representation of the studied dynamic system, the models are usually weighted.The simplest method, namely the model democracy, gives equal weights to all models, while more advancedapproaches base weights on agreement with available observations. Here, we focus on determining weights forvarious versions of an idealized model of the Atlantic Meridional Overturning Circulation. This is done by assessing their performance against synthetic observations (generated from one of the model versions) within a dataassimilation framework using the ensemble Kalman filter (EnKF). In contrast to traditional data assimilation, weimplement data-driven forecasts using the analog method based on catalogs of short-term trajectories. This approach allows us to efficiently emulate the model’s dynamics while keeping computational costs low. For eachmodel version, we compute a local performance metric, known as the contextual model evidence, to compareobservations and model forecasts. This metric, based on the innovation likelihood, is sensitive to differences inmodel dynamics and considers forecast and observation uncertainties. Finally, the weights are calculated usingboth model performance and model co-dependency and then evaluated on averages of long-term simulations.Results show good performance in identifying numerical simulations that best replicate observed short-termvariations. Additionally, it outperforms benchmark approaches such as strategies based on model democracy orclimatology when reconstructing missing distributions. These findings encourage the application of the proposedmethodology to more complex datasets in the future, like climate simulations.